ANALISIS PEMILIHAN SUPPLIER INTERNET SERVICE PROVIDER MENGGUNAKAN METODE FUZZY ANALYTICAL HIERARCHY PROSES (F-AHP) DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) DI PT XYZ - Rizqi Mubaroq (2021)
The development of cellular networks provides opportunities for companies to compete in building an internet service provider. To maintain the feasibility of internet services, internet service providers strive to provide the best quality. This research was conducted to determine the best internet service provider supplier at PT. XYZ uses Fuzzy AHP and TOPSIS methods. In this study, the cut-off point method was used to select the main criteria and sub-criteria consisting of 5 criteria and 19 selected sub-criteria. The AHP method is used to solve a complex problem in the form of a hierarchy and fuzzy logic is used to reduce the uncertainty in making choices. The fuzzy AHP method is used to determine the value of the weight of the criteria and sub-criteria. Based on the calculation of the Fuzzy AHP method, the credibility of the internet service provider becomes the main criterion in the selection of internet service provider suppliers with a weight of 0.305. The results of this study indicate that of the four suppliers consisting of TLKM, IC, X, and MYR, the TLKM supplier was selected as the best alternative using TOPSIS with the highest preference value of 0.8423.